The Legal Status of the Circular Letter of the Ministry of Law Concerning the Appointment of Notaries Related to the Dispute Over Dualism in the Indonesian Notary Association - H. Wira Franciska; Salsabila Sekar Wahri (Journal of Law, Politic and Humanities, 2025)
The issues that will be discussed in this study are regarding the legal position and legal certainty of the Circular Letter of the Ministry of Law and Human Rights number AHU-AH.02-37/2024 concerning the appointment of the Notary position which will be proven through the theory used, namely the theory of dispute resolution and the theory of legal standing. The method used in this study is juridical-normative with the support of interviews. The research approaches used are the legislative approach, the analytical approach, and the conceptual approach. From the results of the research, it can be obtained: 1) Dispute Resolution Against Dualism of PP Management INI was preceded by the implementation of an exam using the Computer Assisted Test (CAT) system as a temporary replacement for the requirements for the appointment of notaries. Meanwhile, through a decree dated January 16, 2025, the government has taken steps to appoint the Chairman of the Central Board of the Indonesian Notary Association. 2) The legal position of the circular is valid, even though it does not have binding legal force such as laws and regulations, the Circular Letter is an important instrument that functions as a tool for policy socialization, implementation instructions, internal coordination, and technical direction.